Microstructural Origins of High Piezoelectric Performance: A Pathway to Practical Lead‐Free Materials. (11th June 2019) - Wu, Haijun; Zhang, Yang; Wu, Jiagang; Wang, John; Pennycook, Stephen J.
Abstract: Piezoelectric materials interconvert between electrical energy and mechanical strain and are widely used for electronic and electromechanical devices. Owing to growing environmental concerns, development of lead‐free piezoelectric materials with enhanced properties becomes of great interest. Key to the academic problem is a lack of fundamental understanding on the actual mechanisms involved at the microscopic (unit cell) level. While it is well known that giant responses occur near structural phase boundaries, and it has long been proposed that polarization rotation and nanodomains are major determinants, so far, atomistic understanding of the origin of the response has come mostly from theoretical simulations. Recently, notable breakthroughs have been achieved in improving the properties of piezoceramics and thin films. Precise mapping of atomic displacements by atomically resolved Z‐contrast imaging has demonstrated that gradual polarization rotation bridges the coexisting nanophases. These structural features, which take place on a length scale of just a few nanometers, now visible through aberration‐corrected microscopy, provide a new pivotal understanding on the outstanding piezoelectric behavior that has been obtained in all systems. They also provide key guiding principles for the development of lead‐free piezoelectrics, especially in the form of thin films, which remain far behind bulk ceramics at the time being. Coexistence of nanophases with flexible interconversion, introduced via phase boundary engineering, holds much promise for achieving high performance in other material systems with phase transitions. Abstract : With aberration‐corrected scanning transmission electron microscopy (STEM), directly seeing and tuning atomic‐scale local polarization inside nanodomains for piezoelectrics has now become possible. Precise mappings of atomic displacements demonstrate gradual polarization rotations among coexisting nanophases. These atomic‐scale structural features provide a new pivotal understanding of the outstanding piezoelectric behaviors that have been obtained for all piezoelectric systems.